Relevance of goal theories to language learning research. (November 2019) - Lee, Minhye; Bong, Mimi
Abstract: As the need to acquire a second/foreign language has increased steadily, a growing body of research has investigated the role of motivation in language education. In this review, we focus on the goal construct, which plays a critical regulatory function in motivational processes. We provide an overview of the two most widely accepted goal theories in motivation literature, the goal-setting and achievement goal theories, and then introduce relevant empirical findings that demonstrate the applicability of these theories to language learning research. We also introduce general motivation theories with a significant bearing on the goal construct, including self-determination theory, future time perspective, and mindset theory. We end this review with the theoretical and practical implications of goal theories in language education and research.